La calidad del servicio educativo y de atención de los Centros Infantiles del Buen Vivir, perspectivas y expectativas de los padres de familia. /estudio de caso en el CIBV “Casita de Luz Nina Wasi” del barrio Monserrat, parroquia el Jordán, cantón Otavalo, provincia de Imbabura - Torres Oña, Yadira Alexandra (2014)
This research work was conducted at the CIBV "Casita de Luz" Monserrat neighborhood, Canton Otavalo, parish Jordan; This was done with the participation of teachers, parents and mothers of the institution and the community. It was necessary to analyze the quality of education and infant care centers for Good Living from the perspectives and expectations of parents; taking into account that early childhood is considered the primary stage in human life, where the development of skills and abilities is power. For this we have taken into account the various theories of development proposed by several authors who have submitted their research, among the highlights are: Piaget, Vygotsky, Ausubel, Dewey, Montessori.